2022
DOI: 10.3126/ajms.v13i1.40486
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and morphometric study of dry scapula, with emphasis on the glenoid fossa and acromion process in Chennai city, South India

Abstract: Background: The morphology and morphometry of the scapula and its glenoid fossa and acromion process play a significant role in the mechanics of shoulder joint. A variable morphology is found in glenoid fossa that has clinical implications. Aims and Objectives: The aim of the study was to evaluate the morphology and morphometry of dry scapula with emphasis on glenoid fossa and acromion process. Materials and Methods: A cross-sectional study was conducted at the department of anatomy, for a period of 6 months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
0
1
Order By: Relevance
“…Outcomes from this study revealed a high similarity with findings from Patel et al regarding the scapula dimensions (i.e., mean length) (135.76±12.85 mm vs. 119.63±8.81 mm (females)/136.03±11.49 mm (males)) [ 14 ]. Slight differences were reported between our study outcomes and the findings of Azhagiri et al (149.58 mm) about regions in South India [ 15 ]. Alternatively, higher scapular dimensions were revealed in a study conducted in Egypt (151.16±10.32 mm) [ 11 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Outcomes from this study revealed a high similarity with findings from Patel et al regarding the scapula dimensions (i.e., mean length) (135.76±12.85 mm vs. 119.63±8.81 mm (females)/136.03±11.49 mm (males)) [ 14 ]. Slight differences were reported between our study outcomes and the findings of Azhagiri et al (149.58 mm) about regions in South India [ 15 ]. Alternatively, higher scapular dimensions were revealed in a study conducted in Egypt (151.16±10.32 mm) [ 11 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The anteroposterior diameter or glenoidal breadth was studied as B = (B1+B2), and their mean value with standard deviation was 21.99 ± 2.76 for the right side and 21.17 ± 2.55 left side, respectively, in the present study. Both height and breadth of our study were slightly less than the observations done by Azhagiri R. et al 2022 12 , Rajani Singh 2020 13 , Alkesan M. et al 2022 14 and Philip S. E. et al 2021 11 . The p value for both sides is almost insignificant, corroborating with Rajani Singh 2020 13 , Alkesan M. 2022 14 .…”
Section: Fig 3: Different Types Of Glenoid Fossacontrasting
confidence: 65%